2015
DOI: 10.1016/j.chemosphere.2014.06.058
|View full text |Cite
|
Sign up to set email alerts
|

History of metal contamination in Lake Illawarra, NSW, Australia

Abstract: Lake Illawarra has a long history of sediment contamination, particularly by metals, as a result of past and current industrial operations and land uses within the catchment. In this study, we examined the history of metal contamination in sediments using metal analysis and (210)Pb and (137)Cs dating. The distributions of copper, zinc, arsenic, selenium, cadmium and lead concentrations within sediment cores were in agreement with historical events in the lake, and indicated that metal contamination had been oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Reservoirs are artificial freshwater ecosystems where pollutants can accumulate in the sediment through multiple pathways, including surface runoff, underground runoff, and atmospheric deposition. Therefore, reservoir sediments are large pools of environmental pollutants and important archives for recording environmental changes in the watershed [1][2][3]. Heavy metals in sediments may have a variety of sources, including rock weathering, traffic exhaust, domestic sewage, chemical fertilizers and pesticides, and wastewater and other wastes from industrial and mining activities [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Reservoirs are artificial freshwater ecosystems where pollutants can accumulate in the sediment through multiple pathways, including surface runoff, underground runoff, and atmospheric deposition. Therefore, reservoir sediments are large pools of environmental pollutants and important archives for recording environmental changes in the watershed [1][2][3]. Heavy metals in sediments may have a variety of sources, including rock weathering, traffic exhaust, domestic sewage, chemical fertilizers and pesticides, and wastewater and other wastes from industrial and mining activities [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Estuaries are among the most important coastal features, both ecologically and with respect to human settlement and use (Ryan, 2003;Schneider et al, 2015a). Along with tropical rainforests and coral reefs, estuaries rank as the world's most productive ecosystems, more productive than both the rivers and the oceans that influence them (Harvey et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Along with tropical rainforests and coral reefs, estuaries rank as the world's most productive ecosystems, more productive than both the rivers and the oceans that influence them (Harvey et al, 1998). Nevertheless, coal-fired power stations are often established on the shores of estuarine lakes in Australia where they may represent a threat to these environments (Batley, 1987;Schneider et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…With the assistance of short-lived radionuclide dating techniques such as 210 Pb and 137 Cs, the study of sediment cores can provide historical records of various influences on the aquatic system by indicating both the natural background levels and the human-induced accumulation of heavy metals on a time scale of about 150 years. A series of studies conducted in the estuarine and coastal areas of Australia (Morelli et al 2012;Schneider et al 2015), India (Janaki-Raman et al 2007), Spain (Alvarez-Iglesias et al 2007), Portugal (Mil-Homens et al 2009), England (Andrewsa et al 2008), Mexico (JaraMarini et al 2008;Ruiz-Fernádez et al 2009), Cuba (Díz-Asencio et al 2009), and China (Qiu et al 2011;Xu et al 2014;Feng et al 2014) have revealed varying degrees of heavy metal enrichment with the local industrial and/or agriculture development, and the anthropogenic input is the principal source for the enrichment.…”
Section: Introductionmentioning
confidence: 99%